2022
DOI: 10.1063/5.0101106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heavy inert ion strikes on cell density-dependent profile variation and distortion during the etching process for high-aspect ratio features

Abstract: Vertical scaling technique faces a physical limitation in 3D NAND device fabrication, even assuming superior etching technology. Another promising scaling technique to increase the storage density is lateral scaling, which increases the number of holes between slit and slit from four to nine and above. However, unpredictable small critical dimension, feature-to-feature variation, and distortion occur. To elucidate the profile deteriorations induced by the lateral scaling, we analyzed the effect of the angular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Wang et al [ 14 ] found an etching mechanism transition from fluorocarbon (FC) film deposition to chemical sputtering in a C F /Ar/O gas mixture environment through HPEM and MCFPM simulation. Kwon et al [ 15 ] investigated the role of heavy ion impact on the feature-to-feature profile of SiO by using a multi-scale computer simulation. They found that heavy ion sputtering reduces the feature-to-feature distortion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [ 14 ] found an etching mechanism transition from fluorocarbon (FC) film deposition to chemical sputtering in a C F /Ar/O gas mixture environment through HPEM and MCFPM simulation. Kwon et al [ 15 ] investigated the role of heavy ion impact on the feature-to-feature profile of SiO by using a multi-scale computer simulation. They found that heavy ion sputtering reduces the feature-to-feature distortion.…”
Section: Introductionmentioning
confidence: 99%
“…Because experimental and computational studies have revealed that ions inside the HAR feature play a significant role in HAR SiO etching [ 13 , 14 , 15 , 16 ], most simulation studies have focused on the validation of technologies for individual control of ion flux and energy. For instance, Kim et al [ 17 ] proved the capability of the individual control of ion flux and energy distribution by varying dual-frequency voltages through a two-dimensional particle-in-cell Monte Carlo collisions (PIC-MCC) simulation.…”
Section: Introductionmentioning
confidence: 99%